Outbreak of Cystoscopy-Related Urinary Tract Infections With Pseudomonas aeruginosa in South Korea, 2022: A Case Series - Beomsoo Kim; Young-Sin Choi; Jun-Koo Kang; Yun-Sok Ha; Seock Hwan Choi; Bum Soo Kim; Hyun Tae Kim; Eun Sang Yoo; Tae Gyun Kwon; Jae-Wook Chung; Tae-Hwan Kim (Urogenital Tract Infection, 2024)
Purpose This study conducted an epidemiological investigation of Pseudomonas aeruginosa urinary tract infections (UTIs) following cystoscopy at Chilgok Kyungpook National University Hospital. Materials and Methods From May 16 to July 15, 2022, among 353 patients who underwent cystoscopy, 6 patients reported febrile UTIs following cystoscopy. They were admitted to the urology department of the hospital after visiting the Emergency Department. P. aeruginosa was found in the urine cultures of 4 of the 6 hospitalized patients. During the epidemiological investigation, no changes were observed in factors such as the reprocessing procedures for endoscopic equipment. Therefore, microbiological tests were performed using environmental samples derived from the endoscopic equipment and cleaning process. Results P. aeruginosa was identified in a dual-enzymatic detergent (EmPower) used during the endoscope cleaning process. After changing the disinfectant and cleaning process, no further bacterial growth was observed in subsequent microbiological tests. Conclusions This study highlights the potential of cystoscopes to serve as reservoirs for bacteria due to inadequate cleaning during the disinfection process. To minimize the risk of infections following cystoscopy, it is important to pay close attention to the reprocessing and cleaning of cystoscopes.